2016
DOI: 10.3233/cbm-160623
|View full text |Cite
|
Sign up to set email alerts
|

Expression of nestin, CD133 and ABCG2 in relation to the clinical outcome in pediatric sarcomas

Abstract: Our analysis represents the first complex study of these three putative CSCs markers together in three different types of pediatric sarcomas and showed their possible prognostic values in these tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 66 publications
2
16
0
Order By: Relevance
“…Chen et al also reported an association between ABCG2 overexpression and poor prognosis for hepatocellular carcinoma in elderly patients [42]. However, a different survey found no significant relationship between ABCG2 expression and the clinical outcomes of pediatric sarcomas [43]. ABCG2 may not be enriched in sarcomas, which would explain this result.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al also reported an association between ABCG2 overexpression and poor prognosis for hepatocellular carcinoma in elderly patients [42]. However, a different survey found no significant relationship between ABCG2 expression and the clinical outcomes of pediatric sarcomas [43]. ABCG2 may not be enriched in sarcomas, which would explain this result.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed to be a marker for neural stem and progenitor cells; thus, it was named nestin: neural stem cell protein. Furthermore, it has been proposed that nestin expression correlates with a poor prognosis in malignancies, such as glioblastoma, lung and renal carcinoma, sarcoma and skin melanoma (Piras et al 2010;Cros et al 2016;Guadagno et al 2016;Li et al 2016;Zambo et al 2016). Nestin was recently classified as a CSC marker found in various tumours of neuroectodermal or mesenchymal origin arising in the brain, oropharynx, pancreas, kidney and muscle (Krupkova et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Nestin was recently classified as a CSC marker found in various tumours of neuroectodermal or mesenchymal origin arising in the brain, oropharynx, pancreas, kidney and muscle (Krupkova et al 2010). Furthermore, it has been proposed that nestin expression correlates with a poor prognosis in malignancies, such as glioblastoma, lung and renal carcinoma, sarcoma and skin melanoma (Piras et al 2010;Cros et al 2016;Guadagno et al 2016;Li et al 2016;Zambo et al 2016). In the latter, nestin expression was associated with more advanced tumour stages and predicted poor survival (Brychtova et al 2007;Piras et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have investigated whether CD133 expression is useful for clinical outcomes, and these studies have shown that CD133 is positively related to poor prognosis in HCC patients [14], that high CD133 levels are associated with shorter survival rates in rhabdomyosarcoma patients [15], and that CD133 expression might be an unfavorable prognosis for ovarian cancer patients [16]. Two meta-analyses have shown that higher CD133 levels are significantly associated with lymph node metastasis, clinical stage, and histopathological grade in colorectal cancer and esophageal carcinoma patients [17, 18].…”
Section: Introductionmentioning
confidence: 99%